Avaliação da política estadual de educação do campo: contribuições para a construção do sentimento de pertencimento da juventude rural no estado do Ceará - Lobo, Francisco Bruno Silva (2020)
This work refers to a research that has the general objective of evaluating the State Policy of Rural Education from its contribution to the construction of the feeling of belonging of Rural Youth. In this sense, the specific objectives are: to describe and analyze the State Rural Education Policy; analyze, from the perspective of rural youth, how the policy described in official documents is being implemented; and investigate possible changes in the personal experience of young people, within the scope of territorial belonging, based on politics. Recognizing the need to establish a broad evaluative look, based on an interpretive approach, based on the hermeneutic paradigm, the In-Depth Assessment is adopted as a theoretical and political perspective, emphasizing the dimensions of content and context. This is an evaluative research of a qualitative nature and can be classified as exploratory and descriptive. The field research was carried out in the 25 de Maio Settlement, municipality of Madalena, Ceará, more precisely at the João dos Santos Oliveira School (João Sem Terra). The approach to the field of research took place between the months of May and August 2019. The research subjects are the young rural students of the school in question, in the context of high school, these being 12 in total; 06 girls and 06 boys. In this sense, the case study was adopted as a methodological approach to investigation. As procedures and instruments for collecting information, bibliographic and documentary research were used; participant observation and realization of field notebook. Aiming to apprehend the subjectivities of the research subjects, individual unstructured interviews were conducted (in depth). Regarding the interpretation of the information collected, this evaluative research establishes its roots in the field of Bardin's content analysis. Thus, it undertakes a wide context analysis involving the Brazilian agrarian scenario within the scope of the recent government agendas and the agrarian question in Ceará. The conceptual bases of the policy under study, its context of formulation and institutional trajectory are analyzed. The research showed the perception that rural young people establish regarding the operationalization of the policy; integrative curriculum components and organicity of the rural school. The construction of the belonging of the rural youths was evidenced as territorial beings from the insertion in the activities that value the rescue of the collective memory; establishing affective ties with the place of origin; and interest in collective engagement and contribution to the territory in which they operate.